Memória da produção editorial científica da EDUFRN: 1962 a 1980 - Pereira, Francisca Sirleide (2012)
It unveils the results of the research in quantity and qualitative Memories of EDUFRN scientific editorial production: 1962-1980, carried out in the Programa de Pós-graduação em Ciência da Informação da Universidade Federal da Paraíba (PPGCI/UFPB). It analyses the scientific editorial production of EDUFRN, imbracing it as artifact memories. We applied the method of documental research according to Jardin (1998) and the thematic oral history, by Arostegui (2006) adding them to the analyse of contents, and documental analyse, by by Bardin (1977). In order to reach our objective we appealed to the theories of collective memory by Halbwachs (2006) and Ricouer (2007); of scientifc divulgation, by Targino (1999) and Bueno (2007); of documantation, by Jardin (1995) and others. We worked with the conception of artifacts of memory, by Gonzaléz de Gomez (2009), Azevedo Neto and Freire (2007) and concluded that the scientific works published by the Publisher, named in this work of documents are plenty of informations and memories. For this reason we called them memory workmanship. We suggest, among other things, that such artfacts could be preserved while cultural public inheritance.